Psychosocial Risk Factors from the Perception of Women Researchers Belonging to the SNI - Lopez, Blanca Estela Aarun; Espinosa, Ana Maria Alejandra Herrera (European Scientific Journal, ESJ, 2018)
This investigation had the objective to identify the perception of women holding PhD degrees awarded by the National Researchers System (SNI) regarding five work environment psychosocial risk factors, stress, burnout, mobbing, work-family integration and gender. A qualitative research was performed involving six female researchers working in either public or private institutions. A content analysis technique was used to process the information procured through a semi-structured interview. Work-related stress was found to be part of their lives determined by excess of work with subsequent physical and emotional manifestations; burnout and mobbing were not a constant as not all had experienced them; work-family integration had not been achieved, often resulting in conflict particularly at a certain stage of life when children were young; and, finally, with regard to gender, there were negative stereotypes concerning the role in their field of research.